1982
DOI: 10.1021/jf00112a027
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin inhibitors and hemagglutinins in beans (Phaseolus vulgaris) and their relationship with the content of tannins and associated polyphenols

Abstract: publications on the subject, especially concerning those legume seeds more often consumed, such as soybeans and common beans. Of these factors, trypsin inhibitors (TI) and hemagglutinins (HA) have been considered as the main ones, although lately the importance of tannins and associated polyphenols has been recognized, since several authors have reported the ability of these components to inhibit the activity of a vast spectrum of enzymes, influencing the digestibility of the diets (Bressani and Elias,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Generally, at higher temperatures, higher phenolic contents were observed; this phenomenon was similarly observed by Fernandez, Elias, Braham, and Bressani (1982), who argued a cleavage of polyphenol polymers occurred, increasing the associated presence of more simple phenolic molecules. In this sense Xu, Ye, Chen, and Liu (2007) reported increasing phenolic acids content in cooked common beans.…”
Section: Total Phenolic Contentsupporting
confidence: 72%
“…Generally, at higher temperatures, higher phenolic contents were observed; this phenomenon was similarly observed by Fernandez, Elias, Braham, and Bressani (1982), who argued a cleavage of polyphenol polymers occurred, increasing the associated presence of more simple phenolic molecules. In this sense Xu, Ye, Chen, and Liu (2007) reported increasing phenolic acids content in cooked common beans.…”
Section: Total Phenolic Contentsupporting
confidence: 72%
“…The hemagglutinative activity decreased with the maturity of the plant, but this tendency was not found in the cultivars Ouro do Vale and Maracanã FERNANDEZ et al 17 observed the agglutination of erythrocyte solutions in crude extracts of the black, white and red common beans until dilution 10 4 and 10 6 ; therefore, CLM showed much lower values (from ND at 2 1 ). However, the toxicity is quite variable among the vegetative species.…”
Section: Resultsmentioning
confidence: 93%
“…The liberated compounds may then contribute higher antioxidant potential when they are considered as a dietary antioxidant. Ferna´ndez, Elias, Braham, and Bressani (1982) also found a significant increase in phenolic compounds after cooking beans under high pressure. Analyzing the level of bioactive compounds in cereal grains before and after hydrothermal processing, Zielin´ski, Kozlowska, and Lewczuk (2001) demonstrated an increase of up to 300% in the content of phenolic acids after extrusion cooking.…”
Section: Article In Pressmentioning
confidence: 79%